2022
DOI: 10.1093/heapro/daab197
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy as a social vaccine in the COVID-19 pandemic

Abstract: Summary The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel virus in the coronavirus family, causing the coronavirus disease (COVID-19). Biomedical vaccines are key but alongside biomedical vaccines, a social vaccine can be similarly useful to prevent infection from SARS-CoV-2, if applied as a health promotion strategy. In order to slow down and control the spread of SARS-CoV-2, applying the social vaccine concept should be considered in parallel. From a health promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
102
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 35 publications
3
102
0
11
Order By: Relevance
“…Our cross-sectional Danish study is a contribution to the ongoing international studies on university students’ DHL [ 21 , 22 , 23 , 24 , 25 ] and the findings from this study provide new knowledge about the vulnerability of students in crisis situations, such as the COVID-19 pandemic, when high DHL is necessary. This knowledge can inform the designers of interventions aiming at strengthening DHL as a social vaccine [ 7 ] to avoid the further spread of COVID-19 among students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cross-sectional Danish study is a contribution to the ongoing international studies on university students’ DHL [ 21 , 22 , 23 , 24 , 25 ] and the findings from this study provide new knowledge about the vulnerability of students in crisis situations, such as the COVID-19 pandemic, when high DHL is necessary. This knowledge can inform the designers of interventions aiming at strengthening DHL as a social vaccine [ 7 ] to avoid the further spread of COVID-19 among students.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is paramount that governments and health authorities implement a well-reasoned and evidence-informed health communication strategy to provide valid and reliable health information concerning the COVID-19 pandemic and support individuals to make health-promoting decisions [ 5 , 6 ]. In this context, health literacy must be understood as a social vaccine, a critical tool in the emergency toolbox of public health action to counteract the effects of the pandemic [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Araujo et al called HL a weapon against the virus [ 31 ]. Recently, Okan et al have even used the term ‘social vaccine’ in relation to HL in the context of the COVID-19 pandemic [ 32 ]. Indeed, many authors of the subsequent studies confirmed a significant association between HL and attitudes and knowledge about preventive measures during the COVID-19 pandemic [ 33 , 34 , 35 , 36 ] or compliance with preventive measures [ 35 , 37 , 38 , 39 , 40 ] in various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the field of health literacy have argued that health literacy has been vastly undervalued and unrecognized in the fight against COVID-19 [ 1 ] and ought to be considered the quintessential “social vaccine” for preventing COVID-19 in populations [ 2 ]. Indeed, as an essential self-management skill and community resource for health, the effects of low population health literacy are likely to be much more pronounced under the current infodemic, in which volumes of disparate quality information are rapidly being disseminated through mediums of public communication, consumption, and information sharing.…”
Section: Introductionmentioning
confidence: 99%